Catástrofe e utopia: a crítica à ideologia do progresso em Benjamin e Bloch e a iconoclastia das lutas contemporâneas - Oliveira, Francisco das Chagas de (2023)
This dissertation examines the concepts of Catastrophe and Utopia, as developed by Walter Benjamin (1892-1940) and Ernst Bloch (1885-1977), in the context of the ascendancy of destructive technics between the outbreak of World War I (1914-1918) and the unfolding of World War II (1939-1945). Conceived as fundamental elements of the Marxist romantic critique of the Ideology of Progress, the concepts of Catastrophe and Utopia are analyzed in a dialogical manner, drawing from the works of Benjamin and Bloch, to achieve a deeper understanding of contemporary social reality. In this regard, the present research investigates the construction and perpetuation of a religious mentality, characterized by a certain "redemptive romantic violence," manifested in the actions of marginalized groups involved in the destruction of historical heritage during the early 21st century. Consequently, the research demonstrates the ongoing existence of this worldview in the discourse of resistance against capitalist modernity, which is reflected in acts of depredation targeting historical monuments associated with the Brazilian colonial era. Throughout the study, we employed documentary analysis, giving priority to traditional Brazilian and international media outlets with a strong digital presence. The incident of the fire at the monument in honor of Borba Gato was used as a poignant example in the context of critically perceiving Brazilian reality. This event resonates with the new contemporary iconoclastic wave and highlights how social movements absorbed the wave of destruction while also taking action. We found that the demands of these movements challenge socioeconomic projects and hegemonic historical-social narratives. Moreover, this contestation is imbued with utopian power, as it recognizes that capitalism poses a threat to the world of life.